If the value of the integral
∫ 0 ∞ x 4 + 1 6 ( x 2 + 4 ) ln x d x
can be expressed as b c π ln a where a is a prime number and c is square free find a + b + c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can also directly replace x by x 4 and add the two to simplify our integral ⌣ ¨
Log in to reply
that;s what i did :) . There is also one very similar problem . ∫ 0 ∞ x 2 + 2 x + 4 ln ( x )
and @Pranav Arora Come one guys, take part in Brilliant Integration Contest - Season 1 like Jatin, @Sudeep Salgia , and @Ronak Agarwal . (>‿◠)✌
Let's start from the formula I derived here : ∫ 0 ∞ 1 + x b x a − 1 d x = b π csc ( b a π ) ( 1 ) Setting x = c t to ( 1 ) , we have ∫ 0 ∞ c b + t b t a − 1 d t = b c b − a π csc ( b a π ) ( 2 ) Differentiating ( 2 ) with respect to a yields ∫ 0 ∞ c b + t b t a − 1 ln ( t ) d t = ∂ a ∂ [ b c b − a π csc ( b a π ) ] ( 3 ) Using ( 3 ) to solve the considered integral by setting b = 4 , c = 2 , and making substitution t ↦ x , then ∫ 0 ∞ x 4 + 1 6 ( x 2 + 4 ) ln x d t = ∂ a ∂ [ 4 ⋅ 2 4 − a π csc ( 4 a π ) ] a = 3 + 4 ∂ a ∂ [ 4 ⋅ 2 4 − a π csc ( 4 a π ) ] a = 1 = 2 2 π ln 2
Put x = 2 t to get our integral as :
I = 2 1 ∫ 0 ∞ ( t 4 + 1 ) ( t 2 + 1 ) l n ( 2 t ) d t
I = 2 1 ∫ 0 ∞ ( t 4 + 1 ) ( t 2 + 1 ) l n ( t ) d t + 2 l n ( 2 ) ∫ 0 ∞ ( t 4 + 1 ) ( t 2 + 1 ) d t
I = I 1 + I 2
I 1 = ∫ 0 1 ( t 4 + 1 ) ( t 2 + 1 ) l n ( t ) d t + ∫ 1 ∞ ( t 4 + 1 ) ( t 2 + 1 ) l n ( t ) d t
In the second integral put z = 1 / t to get :
I 1 = ∫ 0 1 ( t 4 + 1 ) ( t 2 + 1 ) l n ( t ) d t − ∫ 0 1 ( z 4 + 1 ) ( z 2 + 1 ) l n ( z ) d z = 0
I 2 = 2 l n ( 2 ) ∫ 0 ∞ ( t 4 + 1 ) ( t 2 + 1 ) d t = 2 l n ( 2 ) ∫ 0 ∞ ( t 2 + t 2 1 − 2 ) + 2 ( 1 + t 2 1 ) d t
Put t − t 1 = x to get I 2 as :
I 2 = 2 l n ( 2 ) ∫ 0 ∞ x 2 + 2 d x
⇒ I 2 = 2 2 π l n ( 2 )
Hence I = 2 2 π l n ( 2 )
We can also do it using contour integral.
Another approach........... Put x^2 = 4tan(theta).............then, differentiate under the integral sign..........!!!!
Problem Loading...
Note Loading...
Set Loading...
x 4 + 1 6 = ( x 2 − 2 2 x + 4 ) ( x 2 + 2 2 x + 4 )
Hence,
I = ∫ 0 ∞ 2 1 ( x 2 − 2 2 x + 4 ln x + x 2 + 2 2 x + 4 ln x ) d x
Now, Putting x = 2 z ,
I = 4 1 ∫ 0 ∞ ( z 2 − 2 z + 1 ln 2 + ln z + z 2 + 2 z + 1 ln 2 + ln z ) d z
Now, putting z = t 1 ,
I = 4 1 ∫ 0 ∞ ( t 2 − 2 t + 1 ln 2 − ln t + t 2 + 2 t + 1 ln 2 − ln t ) d t
Adding these, we get :
I = ∫ 0 ∞ 4 ln 2 ( ∫ 0 ∞ z 2 − 2 z + 1 1 d z + ∫ 0 ∞ z 2 + 2 z + 1 1 d z )
= 4 ln 2 ( 2 2 3 π + 2 2 π )
= 2 2 π ln 2